Generation of Bessel plasmon-polaritons in metamaterials - Anh, Nguyen Pham Quynh; Kurilkina, Svetlana N. (Journal of the Belarusian State University. Physics, 2019)
In the paper it is developed the theory of Bessel plasmon-polaritons generation in a structure containing a layer of a uniaxial metamaterial separated from the substrate and the external medium by additional isotropic dielectric layers. The dispersion equation for the cases of symmetric and asymmetric structures is obtained and analyzed. It is shown that if a hyperbolic metamaterial possesses an extremely large anisotropy, the Bessel plasmon-polariton generation in the structure is possible for which the longitudinal component of the electric vector increases monotonically inside the metamaterial layer. The dependence of the excitation conditions of Bessel plasmon-polaritons on the thickness of additional layers of the structure is established. It is shown that the implementation of an additional (intermediate or protective) layer in the structure causes a decrease of the central maximum of the Bessel-plasmon-polariton. Meanwhile, it becomes more noticeable for the thick layers. The obtained results can be used while elaborating new devices for surface testing.
Keywords: Bessel plasmon-polariton; metamaterial; metal-dielectric medium; dielectric permittivity; anisotropy